Clement of Alexandria’s Homily "Quis Dives Salvetur?" and Its Pastoral Challenges for Alexandrian Christians - Plátová, Jana (Vox Patrum, 2023)
The article reconsiders the structure of Clement’s writing Quis dives salvetur? and as a consequence questions the traditional designation of this text as a homily. In the first part, the article focuses on the Gospel text quoted by Clement and attempts to explain some of the unusual choices of the text. In the second part, it highlights some pastorally interesting or, on the contrary, controversial aspects of Clement’s interpretation: (a) the use of the Stoic concept of indifferent things, which makes it possible to give emphasis to the freedom of human decision; (b) the thorough justification of the allegorical interpretation of Mk 10, 21; (c) the pastoral project of the “divine business” based on Lk 16, 9 and finally (d) the possibility of a second repentance after baptism justified by the story of the Apostle John.